Quando o Passado nos dá Sementes para Colher Futuros. Partilhar Saberes Locais para Enfrentar Problemas Globais - Marques, Maria Helena A. G. (Trabalhos de Antropologia e Etnologia, 2020)
Agriculture is one of the sectors most directly affected by the impact of climate change. In many regions of the world, such as Portugal, smallholders farmers have developed over generations, agricultural systems adapted to local conditions and based on the diversification of cultivated species and varieties that allow them, even under difficult weather conditions, to guarantee continuous production with scarce resource to external factors of production. Besides the preservation of seeds of local/regional varieties, through their cultivation and dissemination, there is crucial the farmers knowledge mobilization and sharing, particularly among economically vulnerable smallholders facing similar climate problems.